A Suggested Approach for Management of Pediatric Asthma During the COVID-19 Pandemic - Ding, Bo; Lu, Yanming (Frontiers in Pediatrics, 2020)
Asthma is a prevalent pediatric disease causing important health, economic, and emotional burdens around the world. Asthma attacks can be controlled with standardized management, but no cure exists for the disease. Many attacks are triggered by respiratory tract infections and children with basic airway diseases are at high risk for developing severe or critical illnesses. The new COVID-19 pandemic threatens to disrupt children’s asthma control management and we have set out to summarize the main factors that need to be considered by pediatricians treating children with asthma at times like these. We discuss the intrinsic nature of asthma and its treatment, and the effects of irregular treatment giving recommendations such as the use of the WeChat platform and WeChat Official Accounts for follow-ups to improve children's asthma compliance during the pandemic. We also cover the COVID-19 protection strategies, and the importance of stress reduction, a balanced diet, exercise, and the avoidance of known attack triggers for maintaining good control of asthma during the pandemic.